2010
DOI: 10.1088/0004-6256/139/3/865
|View full text |Cite
|
Sign up to set email alerts
|

EVIDENCE FOR a STRONG END-ON BAR IN THE RINGED Σ-Drop GALAXY NGC 6503

Abstract: We use WIYN High-resolution Infrared Camera (WHIRC) H (1.6 µm) band imaging, archival Spitzer, HST, and GALEX data, simulations and data from the literature to argue for the presence of a strong end-on bar in nearby spiral galaxy NGC 6503. The evidence consists of both photometric and kinematic signatures as well as resonant structures present in the galaxy which are most often associated with bars. These include a central peak followed by a plateau in the surface brightness profile, an extreme decrement in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 44 publications
(58 reference statements)
3
10
0
Order By: Relevance
“…The same authors postulate that while this galaxy is possibly one of the rare cases of ring spirals classed as unbarred 2 , it is most likely to actually be barred. Indeed, both the HI velocity field (Bottema & Gerritsen 1997) and near-IR imaging (Freeland et al 2010) support the presence of a strong end-on bar. Moreover, Freeland et al (2010) argue that the previously identified nuclear ring is instead an inner ring spanned in diameter by the bar (Fig.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The same authors postulate that while this galaxy is possibly one of the rare cases of ring spirals classed as unbarred 2 , it is most likely to actually be barred. Indeed, both the HI velocity field (Bottema & Gerritsen 1997) and near-IR imaging (Freeland et al 2010) support the presence of a strong end-on bar. Moreover, Freeland et al (2010) argue that the previously identified nuclear ring is instead an inner ring spanned in diameter by the bar (Fig.…”
Section: Introductionmentioning
confidence: 93%
“…Indeed, both the HI velocity field (Bottema & Gerritsen 1997) and near-IR imaging (Freeland et al 2010) support the presence of a strong end-on bar. Moreover, Freeland et al (2010) argue that the previously identified nuclear ring is instead an inner ring spanned in diameter by the bar (Fig. 1).…”
Section: Introductionmentioning
confidence: 93%
“…Freeland et al (, hereafter F10) present WIYN High‐resolution Infrared Camera (WHIRC) H ‐band (1.6 μm) imaging, in combination with multiwavelength archival imaging and data from the literature, to investigate the origin(s) of the observed star‐forming ring and central σ‐drop. They find a plateau in the surface brightness profile (Freeman Type II behaviour; Freeman ) and several structures in the disc in addition to the star‐forming ring: an end‐on bar, a circumnuclear disc and a nuclear spiral.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of a bar on the rotation curve is a potential complication, as NGC 6503 is now known to possess an end-on bar (Freeland et al 2010). Because the bar is end-on, it is unlikely to significantly affect measurements of either the stellar or gas rotation, and we therefore do not anticipate any significant bias to our results.…”
Section: Potential Complicationsmentioning
confidence: 91%